Pengaruh Kinerja Keuangan, Current Ratio, Debt To Equity Ratio, Working Capital Turnover Terhadap Return On Asset Perusahaan Farmasi Pada Tahun 2019 Sampai Dengan Tahun 2021 - Lailatul Mufidah; Mira Pramudianti (ITScience (Information Technology and Science), 2023)
With the help of financial ratios, the financial performance of a company reveals its level of success or failure as well as how closely its operations comply with the law. This research aims to determine the effect of financial performance on Return on Assets in pharmaceutical businesses from 2019 to 2021 listed on the Indonesia Stock Exchange during the Covid 19 pandemic. Financial performance includes Current Ratio, Debt to Equity Ratio, and Working Capital Turnover. Every pharmaceutical company registered on the IDX from 2019 to 2021 is used as a research object in this quantitative research. The information used is secondary information collected based on records obtained from the IDX. The sampling technique was Purposive Sampling even though the research subjects were 12 companies listed on the IDX in 2019 and 2020. This research shows that Return on Assets is influenced by the Current Ratio, Debt to Equity Ratio, and Working Capital Turnover, as determined by financial performance metrics. Current Ratio and Debt to Equity Ratio both partially influence Return On Assets which is shown simultaneously at a significance level of 0.000, but working capital turnover has no influence.